THE APLICATION OF SCRAMBLE LEARNING MODEL IN THE BASIC WORK SUBJECTS OF AUTOMOTIVE JACKING AND LIFTING MATERIALS At X TKR VOCATIONAL SCHOOL OF STATE 1 PALANGKA RAYA ACADEMIC YEAR 2017/2018 - Ahmad Rifai (Jurusan Pendidikan Teknologi Dan Kejuruan, 2019)
This study aims to find out whether the application of scrambled cooperative learning model could be applied on the Basic Work of automotive material: Jacking and Lifting in class X TKRO of SMK Negeri 1 Palangka Raya Academic Year 2017/2018, by knowing teacher activities, student activities, student responses and knowing student learning outcomes. This study uses descriptive quantitative research methods. The population of this study were all class X TKRO A as many as 32 students and X TKRO B as many as 27 students of SMK Negeri 1 Palangka Raya Academic Year 2017/2018. The sample of this study was class X TKRO B with a total of 27 students. The instruments used in this study were Teacher Activity Observation Sheets, Student Activity Observation Sheets, Student Response Questionnaire, and Learning Outcomes Test (THB). The results of this research: based on the observation sheet of teacher activity at the first meeting, the observation value of teacher activities is 75%, the second meeting is 77.5%, the third meeting is 80%, the fourth meeting is 82.5%, the fifth meeting is 85%, the sixth meeting is 87.5% with an average teacher activity value of 81.25%. The results of the observation sheet are student activities, in the first meeting the student activity value is 71,875, the second meeting is 75, the third meeting is 78.125, the fourth meeting is 81.25 fifth meeting is 84.375, the sixth meeting is 87.5 with an average student activity of 79.69. From the questionnaire of student responses, there were 62.9% of students stated that they were very fond and 37% of students expressed their love when the teacher used the Scramble Learning model on Jacking And Lifting material. KKM 70 standard obtained the value of the average pre-test students only scored 56.94 which 20 students did not complete. But after the teacher used the Scramble Giving model on Jacking And Lifting material, there was an increase in learning outcomes with an average student score of 78.03 with a graduation percentage of 88.88%.